Characteristics and Distribution of Chemical-Biological Parameters in The Seawaters of Eastern Java Sea - Pambudi, Achmad Yogi; Putra, Muhamad Gilang Arindra; Yogaswara, Deny; Yuliardi, Amir Yarkhasy (Journal Omni-Akuatika, 2024)
The Java Sea is influenced by the west and east monsoons, which have an impact on hydrodynamic processes and chemical-biological water quality. Chemical-biological parameters play an important role in the food chain cycle that occurs in these waters. The quality of the eastern Java Sea waters is still limited by chemical-biological parameters, so the characteristics and distribution of these waters can be comprehensively known. chemical-biological. This study aimed to analyze the characteristics and distribution of nitrate, phosphate, oxygen, chlorophyll-A, and NPP parameters in the eastern Java Sea waters. This study used secondary data with daily temporal resolution from January to December 2020. Spatial analysis uses the climatological averaging method for 6 months as a statistical representative of the west monsoon and east monsoon. For each parameter, a vertical analysis was conducted to compare parameter values between the coastal waters of Tuban, Java Sea, and Banjarmasin Waters. Correlation analysis between parameters was conducted using the Pearson correlation method. Nitrate, phosphate, oxygen, chlorophyll-A, and NPP concentrations have temporal and spatial variability. Monsoon factors in Indonesia have a strong influence on the variability of nitrate, phosphate, oxygen, chlorophyll- A, and NPP concentrations. During the east monsoon, the concentration of chemical-biological parameters decreases, while in the west monsoon, the concentration increases and reaches its highest value. Generally, high concentrations occur in the northern and southern parts of the study site, around the coastal areas of Java and Kalimantan. Key Word: Chemical-Biological Parameters, Java Sea, Tuban Waters